DESIGN OF CIRCULAR POLARIZED ANTENNAS USING GENETIC ALGORITHM BASED ON CURVED WIRE ANALYSIS - Mangoud, Mohab A. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
An efficient Method of Moments formulation using curved segmentation (MoM-CS) to model curl and helical antenna structures is implemented and compared to straight wire segmentation code. This integral equation solver is then employed in conjunction with genetic algorithm (GA) to design and optimize complex helical wire antennas such as Tapered Single Helical Antenna (TSHA), Single Elliptical Curl Antenna (SECA) and Tapered Quadrifilar Antenna (TQFA) mounted over infinite ground plane. An optimum gain, VSWR and circular polarization properties that make these antennas suitable to be used in satellite communications systems are obtained. The numerical results show that the hybrid GA/ MoM-CS produces superior antenna designs for such complex geometries with reduced computation time compared to codes that use straight wire segmentations.